KEDUDUKAN HUKUM ANAK SIRI DAN IMPLIKASINYA TERHADAP PERLINDUNGAN KESEJAHTERAAN ANAK - Illy Yanti (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2019)
Position of child by Sirri marriage, based on prevailing crustaceans associated to the mother. This provision makes child by Siri marriage did not get the rights protected by the rule of law. In fact, the legal status of Siri marriage according to Islamic law is valid, just not officially recorded. Determination of child by Siri marriage as young lawful means to protect the rights of children, especially those born through the Siri marriage.